INCORPORATING CEFR PRINCIPLES IN THE DEVELOPMENT OF A HYPERTEXT POETRY LEARNING PLATFORM FOR HIGH SCHOOL STUDENTS - Sinta Indriyani; Lala Bumela Sudimantara (Intensive Journal, 2023)
This study examines the decline of English education in Indonesia and the need for innovative teaching methods to improve students' English proficiency. Despite Indonesia's low ranking on the English Proficiency Index, the traditional teaching approach remains prevalent, which focuses on grammar and vocabulary. The research by Sudimantara (2021) and highlight the benefits of non-traditional approaches such as incorporating nonverbal components. Lian A.-B (2017) also creates an innovative approach called reading for emotion to help students learn English better without worrying about grammar and vocabulary. The study also shows the importance of poetry and literature in English language learning, as proven by Zeman, A., Milton, F., Smith, A., & Rylance, R. (2015) that poetry precedes prose and it is a knowledge management system in the world. The study employed a research and development design to demonstrate the collaboration of using pedagogy, technology, and CEFR to create innovative learning resources that shift students' mindsets and also build the students’ engagement in learning English. This study offers valuable insights into developing innovative learning resources for English language learning in Indonesia, and further research in this area could lead to more effective teaching methods and improve the English proficiency of Indonesian students.